2020
DOI: 10.1371/journal.pntd.0008684
|View full text |Cite
|
Sign up to set email alerts
|

Expanded genome-wide comparisons give novel insights into population structure and genetic heterogeneity of Leishmania tropica complex

Abstract: Leishmania tropica is one of the main causative agents of cutaneous leishmaniasis (CL). Population structures of L. tropica appear to be genetically highly diverse. However, the relationship between L. tropica strains genomic diversity, protein coding gene evolution and biogeography are still poorly understood. In this study, we sequenced the genomes of three new clinical L. tropica isolates, two derived from a recent outbreak of CL in camps hosting Syrian refugees in Lebanon and one historical isolate from Az… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 81 publications
(263 reference statements)
2
13
1
Order By: Relevance
“…Variations in the parasite genome can be associated with its geographical distribution and clinical manifestations, which can influence leishmaniasis management. Interestingly, large-scale research involving a large number of samples and wide geographic range has revealed that genetic diversity is significantly higher than that previously reported ( Bussotti et al., 2018 ; Zackay et al., 2018 ; Franssen et al., 2020 ; Imamura et al., 2020 ; Patino et al., 2020 ; Salloum et al., 2020 ; Zheng et al., 2020 ; Patino et al., 2021 ; Schwabl et al., 2021 ). Recently, single-cell sequencing has demonstrated the presence of several distinct karyotypes within the same Leishmania clone ( Imamura et al., 2020 ; Negreira et al., 2020 ), and multiple-genotype infections have been demonstrated to occur even within the same host and tissue ( Cupolillo et al., 2020 ).…”
Section: Importance Of Genetic Diversity and Genome Plasticity Of Leishmaniacontrasting
confidence: 58%
“…Variations in the parasite genome can be associated with its geographical distribution and clinical manifestations, which can influence leishmaniasis management. Interestingly, large-scale research involving a large number of samples and wide geographic range has revealed that genetic diversity is significantly higher than that previously reported ( Bussotti et al., 2018 ; Zackay et al., 2018 ; Franssen et al., 2020 ; Imamura et al., 2020 ; Patino et al., 2020 ; Salloum et al., 2020 ; Zheng et al., 2020 ; Patino et al., 2021 ; Schwabl et al., 2021 ). Recently, single-cell sequencing has demonstrated the presence of several distinct karyotypes within the same Leishmania clone ( Imamura et al., 2020 ; Negreira et al., 2020 ), and multiple-genotype infections have been demonstrated to occur even within the same host and tissue ( Cupolillo et al., 2020 ).…”
Section: Importance Of Genetic Diversity and Genome Plasticity Of Leishmaniacontrasting
confidence: 58%
“…tropica is a heterogeneous species complex with a broad geographical distribution across Africa and Eurasia [3,6,7] that causes mainly CL, though visceral leishmaniases has been reported [8,9]. L. tropica is typically an anthroponotic disease, though zoonotic transmission may be possible as well [10][11][12]. Although the burden of leishmaniasis is decreasing globally, regions with L. tropica have increasing rates due to local conflicts and associated population displacement, migration and relocation [3], which exacerbates incorrect CL diagnoses and inadequate access to appropriate healthcare and treatments.…”
Section: Introductionmentioning
confidence: 99%
“…L . tropica is typically an anthroponotic disease, though zoonotic transmission may be possible as well [ 10 – 12 ]. Although the burden of leishmaniasis is decreasing globally, regions with L .…”
Section: Introductionmentioning
confidence: 99%
“…Amplification targets are either genomic (nuclear) DNA—such as the small subunit (18S) rRNA gene ( Guillaume et al, 1992 ), the internal transcribed spacer 1 (ITS1), mini-exon regions, the tubulin gene ( Luis et al, 1998 ), and heat shock protein 70 ( Garcia et al, 2004 ) or extrachromosomal DNA, such as repetitive kinetoplast DNA mini-circles and cytochrome b ( Belli et al, 1998 ; Luyo-Acero et al, 2004 ). Up to now, and as far as is known, whole genome sequencing is still as the most advanced and developed technique for the identification of varies species, as it due to the fact that it is with the highest sensitivity and specificity ( Salloum et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%